2019
DOI: 10.3390/ijms20081808
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin: New Insights into an Ancient Ingredient against Cancer

Abstract: Cancer patients frequently use complementary medicine. Curcumin (CUR) and its derivates (from the extract of Curcuma longa L.) represent some of the most frequently used ones, having a long history in traditional Asian medicine. CUR was demonstrated, both in vitro and in vivo, to have significant anti-inflammatory effects, thus potentially counteracting cancer-promoting inflammation, which is a hallmark of cancer. CUR modulate a plethora of signaling pathways in cancer cells, comprising the NF-κB (nuclear fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 65 publications
2
97
0
2
Order By: Relevance
“…However, being similar to other antioxidants including vitamin E, vitamin C, and carotenoids, curcumin has been found to show double-edged roles in the level of intracellular ROS, which appeared to be highly dependent on the cell type [30][31][32]. Curcumin has been reported to elevate ROS levels in multiple cancer cells [30][31][32]. In this study, in line with the well-accepted anti-oxidative activity of curcumin in normal and non-malignant cells [29][30][31][32], 4-week exposure of rats to 40 mg/kg ACR markedly enhanced the level of MDA (an essential biomarker of oxidative stress and lipid peroxidation), decreased the content of GSH (a biologically important intracellular thiol acting as a free radical scavenger) and the activities of SOD and GSH-Px (two important antioxidant enzymes) in the brain tissues.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, being similar to other antioxidants including vitamin E, vitamin C, and carotenoids, curcumin has been found to show double-edged roles in the level of intracellular ROS, which appeared to be highly dependent on the cell type [30][31][32]. Curcumin has been reported to elevate ROS levels in multiple cancer cells [30][31][32]. In this study, in line with the well-accepted anti-oxidative activity of curcumin in normal and non-malignant cells [29][30][31][32], 4-week exposure of rats to 40 mg/kg ACR markedly enhanced the level of MDA (an essential biomarker of oxidative stress and lipid peroxidation), decreased the content of GSH (a biologically important intracellular thiol acting as a free radical scavenger) and the activities of SOD and GSH-Px (two important antioxidant enzymes) in the brain tissues.…”
Section: Discussionmentioning
confidence: 93%
“…ACR exposure has been demonstrated to result in a disturbance in the balance between the free radical formation and elimination, the latter of which is mediated by antioxidant systems [11,12]. The phenolic structure in curcumin confers electron-capturing properties, which destabilize ROS, explaining the wellaccepted antioxidant effects [30]. However, being similar to other antioxidants including vitamin E, vitamin C, and carotenoids, curcumin has been found to show double-edged roles in the level of intracellular ROS, which appeared to be highly dependent on the cell type [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the high lipophilicity of curcumin has led to too low oral bioavailability, chemical stability, and intracellular concentrations to make the results from clinical studies evaluating its anticancer activity reliable. 204 This has led to attempts to increase the overall anticancer activity of curcumin by introducing structural modifications in the molecule that would improve its selectivity towards cancer cells as well as its bioavailability and/or stability, or to use delivery systems that would improve its physicochemical properties. 117 The active ingredients from other Zingiberacea species may conceivably also pose such problems which may be solved through comparable strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical trials have shown the efficacy of curcumin as anti-cancer agent in several types of cancer including pancreatic, colorectal, cervical, oral and breast cancer [282,283]. However, clinical studies documenting the inhibitory effects of curcumin in PCa is scarce.…”
Section: Clinical Trialsmentioning
confidence: 99%